Integrated methods for understanding and monitoring the loss of coastal archaeological sites: The case of Tochni-Lakkia, south-central Cyprus. (April 2017) - Andreou, Georgia M.; Opitz, Rachel; Manning, Sturt W.; Fisher, Kevin D.; Sewell, David A.; Georgiou, Artemis; Urban, Thomas
Abstract: Previous research on the environment of island and coastal areas has demonstrated that erosion substantially affects coastal archaeological site preservation and can lead to the loss of important information regarding past trade and maritime activities. These same at risk coastal archaeological loci are central to much current archaeological focus on networks and connectivity. In practical and theoretical terms, this places significant stresses on local governments and archaeologists, who are trying to monitor rapidly deteriorating cultural heritage and rescue information vital to future research. Beyond ad hoc observations, rigorous methods to quantify such issues have rarely been developed in the archaeology of the Eastern Mediterranean, including the island of Cyprus. In this paper we demonstrate an integrative method, which employs historic aerial photographs and laser scanning to illustrate, quantify and monitor coastline change and its impact on cultural heritage since the industrialisation of the south-central coast of the island in the mid-20th century CE. Highlights: Aerial photography and TLS employed to monitor eroding archaeological sites. Aerial photography shows significant loss of land on archaeological site. TLS shows local variability in the rate of coastal erosion.